Model Pengabdian Masyarakat Berbasis Kawasan - Fakhruddin, Fakhruddin (STAIN Curup, 2018)
Research problems increase community empowerment through the process of human capital and physical capital in the area around the community. The research objective is to develop a model that is supported by the concept of theoretical development. This research focuses on